2018
DOI: 10.5507/bp.2017.049
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological correlation of tumor-associated macrophages in Ewing sarcoma

Abstract: Aims. Tumor-associated macrophages (TAMs) are known markers playing complex roles in tumorigenesis. However, the function of TAMs in a variety of malignancies is not yet fully understood. The aim of this pilot study was to quantify the density of TAMs in Ewing sarcoma and to determine the correlation between TAMs and clinicopathological parameters. Methods. Using immunohistochemistry, the expressions of CD68 and CD163 were examined in 24 tissue samples of Ewing sarcoma of bone. The density of CD68 and CD163-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…A previous study revealed that BCL2 interacted with BCLXL to escape PARP inhibitor toxicity in ES [33]. The density of CD68-positive Tumor-associated macrophages was found in ES tissue samples and statistically correlated with clinical parameters [34]. Meanwhile, TEK and VEGFC were reported their expression was upregulated in ES which may allow the development of sarcoma subtype-targeted therapeutics [35,36].…”
Section: Discussionmentioning
confidence: 92%
“…A previous study revealed that BCL2 interacted with BCLXL to escape PARP inhibitor toxicity in ES [33]. The density of CD68-positive Tumor-associated macrophages was found in ES tissue samples and statistically correlated with clinical parameters [34]. Meanwhile, TEK and VEGFC were reported their expression was upregulated in ES which may allow the development of sarcoma subtype-targeted therapeutics [35,36].…”
Section: Discussionmentioning
confidence: 92%
“…Some studies suggest a positive impact of polarized macrophages with an M1 phenotype [ 74 ], but others have found no clear correlation with survival [ 75 ]. Some studies have even reported longer survival rates in osteosarcoma [ 76 ] and ES [ 77 ] patients with a high density of M2-like TAMs.…”
Section: Immunogenicity Of Sarcoma: Anti-tumor Response and Biomarkersmentioning
confidence: 99%
“…However, a recent study based on the most important cohort of osteosarcoma patients from the OS2006 clinical trial has demonstrated that the presence of CD163 + M2-polarized macrophages is crucial for the inhibition of osteosarcoma progression [35]. In contrast, macrophages do not seem to play such a role in Ewing sarcoma development and patient survival [39,40]. Moreover, M2-polarized macrophages contribute to the exhaustion of T lymphocytes infiltrating the tumor, reducing their proliferation and secretion of pro-inflammatory cytokines [41].…”
Section: Tumor Microenvironment: Crucial Role In Bone Sarcoma Tumomentioning
confidence: 99%
“…However, as described above, it remains difficult to conclude about the role of M2-polarized macrophages in osteosarcoma progression, probably because of the difficulty to clearly identify the different TAMs subtypes in tumors and by the fact that, in contrast to the binary M1/M2 subtype, TAMs correspond to several distinct populations that often share features of both subtypes [164]. In Ewing sarcoma, a first study has initially described a correlation between macrophages infiltrate and poor prognosis but a second one did not observe any correlation between CD68 + macrophages and survival [39,40]. The canonical Wnt/β-catenin signaling pathway seems to drive the polarization of macrophages in cancers.…”
Section: Wnt/β-catenin Pathway and The Bone Tumor Microenvironmentmentioning
confidence: 99%